English senior students' gramatical competencies at Centro Regional Universitario de Veraguas (CRUV) - Gallego Zapata, Jhon Esteban; Sanjur Rodríguez, Nadila (Santiago, Panamá : Centro Regional Universitario de Veraguas, 2021)
General objective: To examine the grammatical competencies, senior students of the English careerat Centro Regional Universitario de Veraguas handle after four years of exposure to the languaje. Specific objetives: To identify the strenghts and weaknesses of seniors in the typs of sentences, clauses, and phrases. To detemine the proper recognition of English modals by seniors. To identify the proper application of verbs in different activa and passive sentences. To determine the level of aplication of conditional markers in English sentences.
"Submitted in partial fulfillment of the requierements for the degree of Bachelor in Humanities with specialization in English in the University of Panama, CRU-Veraguas". -- Página de título.
Keywords: COMPETENCIA Y DESEMPEÑO (LINGUISTICA); LENGUAJE Y LENGUAS -- PRUEBAS DE APTITUD; INGLES -- ENSEÑANZA SUPERIOR; COMPETENCIA COMUNICATIVA; LENGUAJE Y EDUCACION -- PANAMA; ESTUDIANTES DE EDUCACION SUPERIOR -- PANAMA -- VERAGUAS (PROVINCIA) -- EVALUACION; INGLES -- TESIS Y DISERTACIONES ACADEMICAS